The Roles of Person-Job Fit and Job Satisfaction on Work Engagement in Employees of Company X Semarang - Aidina, Nabila Rahma; Prihatsanti, Unika (Universitas Negeri Semarang, 2022)
The study aims to determine the role of a person-job fit and job satisfaction on work engagement. Work engagement is the ability of individuals in organizations that are positively characterized by energy outfits both physically and mentally and substantial work involvement. Person-job fit is an individual assessment of the suitability between the ability of employees and work demands and the suitability of individual needs and what can be given by the job to employees. Then, job satisfaction is a feeling of happiness or unhappiness that employees feel at work done by looking at aspects of conditions that exist in work. It is quantitative research. Samples are 116 employees taken by population sampling. The measuring instrument used uses the Work Engagement scale (25 Items, α = 0.87), Person-job fit Scale (12 items, α = 0.96), and Job Satisfaction Scale (12 Items, α = 0.97). Data were analyzed by using multiple regression analysis, with the results showing a positive role in person-job fit and job satisfaction on work engagement(RX = 0.37 with; p <.0.00). These results indicate that there is a significant positive role in Person-job fit and job satisfaction on work engagement. Person-job fit and Job Satisfaction made a compelling contribution of 14.3% on work engagement.